2013
DOI: 10.1097/dcr.0b013e3182a39959
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Negative Pressure Wound Therapy Significantly Reduces Surgical Site Infection in Open Colorectal Surgery

Abstract: Incisional negative pressure wound therapy appears to reduce surgical site infection in open colorectal surgery. Further study may be helpful to identify patient populations who would have the greatest benefit from this technique(see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A115).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 19 publications
3
81
0
1
Order By: Relevance
“…Several interventions to reduce wound complications have been assessed, including pre-surgical antibiotic treatment and surgical site preparation,[2, 12] maintenance of normothemia, [13, 14] subcutaneous drain placement or suture closure, [1520] subcuticular skin closure,[2124] retention sutures,[25] wound protection devices,[26] negative pressure dressings[27] and skin sealants. [28] The results of these studies have been conflicting; many limited to obstetrical patients or have used varying definitions of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Several interventions to reduce wound complications have been assessed, including pre-surgical antibiotic treatment and surgical site preparation,[2, 12] maintenance of normothemia, [13, 14] subcutaneous drain placement or suture closure, [1520] subcuticular skin closure,[2124] retention sutures,[25] wound protection devices,[26] negative pressure dressings[27] and skin sealants. [28] The results of these studies have been conflicting; many limited to obstetrical patients or have used varying definitions of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It delivers intermittent or continuous negative pressure (ranging from <50mmHg to >125mmHg) to the wound site which is covered with a foam or gauze dressing and sealed with an occlusive drape. Success has been reported in complex wounds 35 with emerging evidence to show that its use in high risk, post-operative incisions prevents SSIs [36][37][38][39][40] . The likely modes of action are through holding wound edges together (thereby reducing the likelihood of surgical dehiscence), stimulation of perfusion, reduction of lateral tension, haematoma and oedema, and protection of the surgical site from exogenous sources of micro-organisms.…”
Section: Negative Pressure Wound Therapy (Npwt)mentioning
confidence: 99%
“…In such situations, NPWT is often applied. A study in 2013 showed that the use of NPWT in open colorectal surgery significantly reduces the SSI rate from 29.3% to 12.5% ( p < 0.05) [54].…”
Section: 9mentioning
confidence: 99%